2021
DOI: 10.1016/j.ijedudev.2021.102436
|View full text |Cite
|
Sign up to set email alerts
|

Schooling progress, learning reversal: Indonesia’s learning profiles between 2000 and 2014

Abstract: Highlights We use nationally representative data to create mathematics learning profiles for Indonesia. We compare student learning levels and changes in learning from 2000 to 2014 to curriculum expectations. Students’ mastery of basic skills is low. Over 14 years, learning declined by approximately 0.25 standard deviations. The average child in grade 7 in 2014 had learned as much as the average child in grade 4 in 2000. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
2
28
0
5
Order By: Relevance
“…Third, a more subtle point is that the learning profile by grade need not be linear and could be concave (additional years of schooling produce less learning gain at higher grades) and hence increases in average grade attainment that push more children through higher grades could have little or no impact on cohort learning outcomes. Beatty et al (2021) demonstrate exactly this phenomenon in Indonesia as they show that the gains in mastery of simple arithmetic are nearly completely flat past grade 6. Hence, the quite substantial expansion between 2000 and 2014 of grade attainment in Indonesia produced zero increase in cohort mastery of arithmetic.…”
Section: Ii)mentioning
confidence: 60%
“…Third, a more subtle point is that the learning profile by grade need not be linear and could be concave (additional years of schooling produce less learning gain at higher grades) and hence increases in average grade attainment that push more children through higher grades could have little or no impact on cohort learning outcomes. Beatty et al (2021) demonstrate exactly this phenomenon in Indonesia as they show that the gains in mastery of simple arithmetic are nearly completely flat past grade 6. Hence, the quite substantial expansion between 2000 and 2014 of grade attainment in Indonesia produced zero increase in cohort mastery of arithmetic.…”
Section: Ii)mentioning
confidence: 60%
“…The circular regulates, among other things, that face-to-face learning in class is replaced by Distance Learning, national exams are abolished, there is leeway in completing curriculum achievements for grade promotion and graduation. Beatty et al, (2021) found a large gap between students' abilities and the standards set by the national curriculum, that learning declined over the course of 14 years. The average 7th grader in 2014 achieved the same numerical mastery as the 4th grader's average in 2000.…”
Section: Educational Problems Before and During The Covid-19 Pandemicmentioning
confidence: 98%
“…( Agostinelli et al, 2022 , Amato and Anthony, 2014 , Arceo-Gómez et al, 2022 , Bansak and Starr, 2021 , Beatty et al, 2021 , Boruchowicz et al, 2023 , Cas et al, 2014 , Corak, 2001 , Crawfurd, 2021 , Dietrich et al, 2021 , Filmer and Pritchett, 2001 , Gertler et al, 2004 , Hernández-Bringas, 2020 , Hevia et al, 2022 , Hillis et al, 2021 , Jaume and Willén, 2019 , Jordan et al, 2021 , Kuhfeld et al, 2020 , Lichand et al, 2021 , Meng and Zhao, 2021 , Miranda-López, 2018 , Orlov et al, 2021 , Poirier et al, 2020 , Pritchett and Justin Sandefur, 2020 , Prix and Erola, 2017 , Ramírez-Raymundo et al, 2021 , Rivera-Hernandez et al, 2021 , Rodriguez-Planas, 2020 , Rodriguez-Abitia, 2021 , Sacerdote, 2012 , Santibañez and Cassandra, 2021 , Steele et al, 2009 , Wittenberg and Liebbrandt, 2017 )…”
Section: Uncited Referencesmentioning
confidence: 99%